STUDIES ON SEED BORNE MYCOFLORA AND EFFECT OF BIOAGENTS AND FUNGICIDES ON WHEAT SEED HEALTH - P. R. BHOYAR; V. D. CHANDANKAR; V. L. BAGDE; DIPALI B. BORKAR; J. S. SONONE (The Bioscan, 2014)
The study revealed that, untreated and pre-treated seed samples exhibited association of eight fungi Viz Alternaria altermata; Alternaria triticina; Aspergillus flavus; Aspergillus niger; Bipolaris sorokiniana; Curvularia lunata; Drechslera tetramera and Fusarium semitectum belonging to six genera. Less association of seed borne fungi was exhibited by pre-treated seed samples over untreated ones. For arresting the mycelia growth fungicidal seed treatments Viz. Thiram (0.3%), Carbendazim (0.1%), Thirum + Carbendazim (2:1) and Carboxin (0.2%) were found significantly superior over rest of the treatments. Increased seed germination, shoot and root length and seedling vigor index was observed in Thirum + Carbendazim (2:1) and Carboxin (0.2%) seed treatments followed by Tricoderma harzianum Rifai seed treatment.